Factors related to information and communication technologies adoption in small businesses in Colombia - Julián Durán; Rubén Castillo (Journal of Innovation and Entrepreneurship, 2023)
This study is an analysis of how a set of factors influenced the decision to adopt information and communication technologies (ICTs) in small businesses in Colombia; for this purpose, a logistic modeling is applied, wherein the explained variable represents the companies' decision to adopt ICTs. The main explanatory elements include demographic aspects of the owner, the company characteristics, and the legal practice of the company and its social capital. Data from the Microbusiness Survey 2019 conducted by the National Administrative Department of Statistics of Colombia were employed. The results show that traits such as owner age and gender affect adoption. Furthermore, variables such as the age and size of the company, the amount of computer equipment, business formalization practices, and social capital influence the use of these technologies. Therefore, it follows that the individual features of business owners are also determinants of technology adoption, and their inclusion becomes essential to supplement the analysis of these issues. In addition, the study supports the evidence that the acceptance of these technologies is positively related to the business size and infrastructure. By exploring, for example, the business formalization factor, a positive effect is obtained; consequently, the implementation of legal practices is linked to the ICT use. Thus, some of the areas for policy implementation would be, on one hand, the endowment of computer equipment, since it is a critical aspect in these small businesses, for which a subsidy policy for the acquisition of devices would be useful. In addition, the promotion of business formalization practices could lead to an improvement in the firm's culture of technology use.
Keywords: 650; Information and communication technology; Small businesses; Technology adoption